The development of assessment framework for construction sustainability - Mohamad Rashideh, Waleed; Said, Ilias; Osman, Omar (2008)

(untitled)
Sustainability of construction firms is closely linked to its ability to procure projects that will generate sufficient turnover over time. The uncertainty concerning future procurement of projects remains the primary concern of any construction firm. Whilst this factor cannot be overcome in one single effort, there is no certainty that projects can continue to be procured if the construction firm are not well equip to face the challenges to remain competitive, innovative and is capable of strategically positioning itself to remain in business and thus sustaining its presence in the industry. The issue of the firm's sustainability is also closely linked to the general facets of sustainable development may exist in parallel; the main dominant thrust is sustainability and sustainable development may exist in parallel; the main dominant thrust is sustainability. A firm can sustain itself of it wholly adopts the concept of sustainable development; whilst maintaining its relevance in the industry it is operating. The objective of this paper is to analyze the frameworks, concepts and approaches of sustainability of construction firms that are embedded in social, economic and environment. The findings of this paper can provide insights for further research in understanding sustainability of constriction firms.